Why kids love (and hate) school : reflections on difference - Jones, Steven P. (Steven Paul), 1955-; Sheffield, Eric C.; Academy for Educational Studies (U.S.) (Gorham, ME : Myers Education Press, 2018)
The authors of Why kids love (and hate) school addresses the following questions: How do contemporary educational theories, policies, and practices impact the manner in which historically marginalized students perceive their schooling experiences? What theories, policies, and practices lead diverse students to hate school? Love school? Feel ambivalent about school? What might be done to create a love of school among these students as opposed to a hatred of school? Approaching these questions from a variety of perspectives, this collection consists of theoretical discussions, personal reflections, research reports, and policy suggestions sourced in the experiences of our most vulnerable students with an eye to making schools places all students might love rather than hate. The essays take up these issues from the perspective of poverty, gender, race, ethnicity, ability, language, and religion, among others. These essays also provide practical advice for teachers and administrators - both practicing and pre-service - for making classrooms and schools spaces that would encourage our students to say, "I love school." As teachers, administrators, university faculty, and researchers, the authors of this collection bring interesting and diverse viewpoints into the discussion
Introduction : why kids love (and hate) school / Steven P. Jones & Eric C. Sheffield -- "Everybody's listening" : when learning is relevant / Jesse Moya -- We really hated school : the journey of two Black PhDs from alienation to transformation / De'Andre Shepard & Kalvin DaRonne Harvell -- Meeting the needs of Muslim learners in an Islamophobic era / Parisa Meymand -- Classes where "kids learn/don't learn a lot" : a study of Mexican American adolescents' voices / Janine Bempechat, Margarita Jimenez-Silva, Jin Li, & Susan D. Holloway -- The power of schools to redirect pathways : supporting students' love of learning across time and place / Eréndira Rueda -- Under the school roof, inside classroom walls : the power of place-based plot patterns to shape school stories of happiness or humiliation for students / Kathy Carter, Amanda Sugimoto, Kathleen Stoehr, & Griff Carter -- Kids love a classroom for everyone / Rob Schulze -- Forgotten learners : academically strong kids in struggling schools / Jeanne Carey Ingle -- Chain link poetry / Robin Brandehoff -- Alternative education programs : changing our vantage point / Lynn Hemmer & Michael Watson -- Listening to the voices of our students : a framework for engagement in science / Rachelle A. Haroldson -- Restorative practices : beyond sensitization to building skills and organizational change / Robert C. Chalwell Jr.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Children with social disabilities -- Education -- United States; Children with social disabilities -- United States -- Attitudes; Children of minorities -- Education -- United States; Children of minorities -- United States -- Attitudes; Enfants socialement défavorisés -- Éducation -- États-Unis.; Enfants socialement défavorisés -- États-Unis -- Attitudes; Enfants issus des minorités -- Éducation -- États-Unis.; Enfants issus des minorités -- États-Unis -- Attitudes; EDUCATION -- Administration -- General; EDUCATION -- Organizations & Institutions; Children of minorities -- Education; Children with social disabilities -- Attitudes; Children with social disabilities -- Education; United States; Electronic book